Safely Decreasing Rigid Bronchoscopies for Foreign-Body Aspiration in Children: An Algorithm for the Emergency Department - Haller, Layla; Barazzone-Argiroffo, Constance; Vidal, Isabelle; Corbelli, Regula; Anooshiravani-Dumont, Mehrak; Mornand, Anne (European Journal of Pediatric Surgery, 2018)
Introduction Rigid bronchoscopy was traditionally performed in the management of foreign-body aspiration (FBA). More recently, since development of a less invasive method, flexible bronchoscopy has been proposed in some centers for the management of FBA. For the past few years, we have applied a decisional algorithm, privileging flexible bronchoscopy for diagnosis and, in some cases, for extraction of foreign body (FB). Our aims are first to analyze our current management of FBA and second to examine the bronchoscopic findings and complications.Materials and Methods Retrospective medical chart review of all patients with clinical suspicion of FBA who underwent bronchoscopy (flexible and/or rigid) from 2009 through 2014.Results An FB was found in 23 (33%) of the 70 patients included in the study (45 boys, 25 girls; median age: 21.5 months). Diagnosis of FBA was made on first intention in 22/23 (96%) and extraction was performed in 7/23 (30%) by flexible bronchoscopy. Rigid bronchoscopy was necessary for the extraction of the 16/23 (70%) remaining FBs. The rigid procedure was performed as first intention in only two (3%) patients, and one of the two was negative. Among the clinical signs of FBA, none were > 90% specific except for apnea (100%), but which was poorly sensitive (22%). Seven clinical and radiologic signs were found to be significantly different between FB+ and FB− groups: sudden choking, cyanosis, apnea, decreased breath sounds, atelectasis, mediastinal shift, and air trapping. Conversely, when none of these symptoms or signs and no clear history of sudden choking were present (in 15/70 patients), no FB was found. No life-threatening complications or death were observed.Conclusion Our current management of FBA allows us to avoid almost all negative rigid bronchoscopies. In addition, we identified some symptoms and clinical and radiologic signs whose absence was highly predictive of negative bronchoscopy. We propose a novel algorithm for management of FBA that will help decrease the number of negative bronchoscopies.
Keywords: child; foreign body; aspiration; management; flexible bronchoscopy